The Influence of Islamic Religious Education Teachers' Personality Competence on Students' Morals: A Case Study at State Senior High School - Nusrial, Nusrial; A. Rahman, Siti Noor Mawar; Abdulmumini, Abdulmumini (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study is to examine the influence of Islamic Religious Education teachers' personality competence on the moral development of students at State Senior High School 2 Jambi City, using a quantitative approach to provide empirical evidence and identify key factors contributing to student character formation. Methodology: This study uses a quantitative research approach with standardized questionnaires as the primary data collection tool. The sample consists of 60 students and 4 Islamic Religious Education teachers, selected through simple random sampling. Data analysis is conducted using SPSS software for descriptive statistics, correlation tests, and regression analysis to identify causal relationships between variables. Main Findings: This study found that the personality competence of Islamic Religious Education teachers significantly influenced student morale at State Senior High School 2 Jambi City, with a beta coefficient of 0.65 (p < 0.001). The average score of teacher personality competence was 4.2, and student morale was 4.0, indicating a high category. Novelty/Originality of this study: This study provides novelty by quantitatively revealing the direct influence of the personality competence of Islamic Religious Education teachers on the formation of student morals, as well as identifying the aspect of teacher role models as a dominant factor in supporting character education in schools.